Measuring the Impact of an Open Educational Resource and Library e-Resource Adoption Program Using the COUP Framework - Davidson Squibb, Sara; Salmon, Elizabeth; Yan, Yueqi (International Review of Research in Open and Distributed Learning, 2023)
Grant programs that foster the use of open educational resources (OER) significantly reduce undergraduate student spending on textbooks per semester. The Zero-Cost Course Materials (ZCCM) grant program at the University of California, Merced (UC Merced), eliminated text costs and ensured access to course materials by replacing required commercial materials with OER and library licensed e-resources. The present study applies the COUP framework (cost, outcomes, usage, and perceptions) to evaluate the ZCCM program. The ZCCM program resulted in student cost savings and did not negatively impact student outcomes. Students in ZCCM courses demonstrated higher rates of course completion than students enrolled in previous sections. For the outcomes of final course grade, passing with a C− or better, and number of credit hours enrolled in, findings were comparable between the cohorts. Student usage and perception of course materials were gathered using a survey. Though students reported favorable views of zero-cost materials, they reported using them less frequently than commercial texts. This research contributes to a growing body of literature that confirms beneficial cost savings for students using zero-cost materials without jeopardizing students’ success.